New Mechanism for Long Photo‐Induced Enhanced Raman Spectroscopy in Au Nanoparticles Embedded in TiO2. Issue 25 (26th May 2022) - Brognara, Andrea; Bricchi, Beatrice R.; William, Ludovic; Brinza, Ovidiu; Konstantakopoulou, Maria; Bassi, Andrea Li; Ghidelli, Matteo; Lidgi‐Guigui, Nathalie
Abstract: The photo‐induced enhanced Raman spectroscopy (PIERS) effect is a phenomenon taking place when plasmonic nanoparticles deposited on a semiconductor are illuminated by UV light prior to Raman measurement. Results from the literature show that the PIERS effect lasts for about an hour. The proposed mechanism for this effect is the creation of oxygen vacancies in the semiconductor that would create a path for charge transfer between the analyte and the nanoparticles. However, this hypothesis has never been confirmed experimentally. Furthermore, the tested structure of the PIERS substrate has always been composed of plasmonic nanoparticles deposited on top of the semiconductor. Here, gold nanoparticles co‐deposited with porous TiO2 are used as a PIERS substrate. The deposition process confers the nanoparticles a unique position half buried in the nanoporous semiconductor. The resulting PIERS intensity is among the highest measured until now but most importantly the duration of the effect is significantly longer (at least 8 days). Cathodoluminescence measurements on these samples show that two distinct mechanisms are at stake for co‐deposited and drop‐casted gold nanoparticles. The oxygen vacancies hypothesis tends to be confirmed for the latter, but the narrowing of the depletion zone explains the long PIERS effect. Abstract : Photo‐induced enhanced Raman scattering (PIERS) is a special case of surface enhanced Raman spectroscopy where the Raman scattering is enhanced after UV irradiation for about an hour. A new material is proposed where Au nanoparticles are embedded in TiO2 . This work reports the duration of the PIERS effect is significantly longer (8 days) and proposes a new mechanism based on cathodoluminescence results.